The condition of suffering and happiness with the perspective of loka-dhamma - Thongputtamon, Miss Notnargorn (The Journal of International Buddhist Studies College, 2023)
This article aims to study the condition of suffering and happiness with the perspective of Loka-dhamma. According to the study, it was found that the condition of suffering and happiness is the feeling. They consist of nature in human life. Loka-dhamma is a natural law. Humans must meet up within the course of a lifetime. Stupid people trying to engage with it and never get away. The Buddha saw that the people who are developing liberating insight can get free from this chain of life. Thus, the perspective of Loka-dhamma can make themselves up to know the right way. This concept dealing with seeing the truth. In addition, with the perspective of loka-dhamma, those who get a touch of this knowledge would do well in releasing themselves from physical and mental suffering, and practice of perfection in Kamma, well-meaning of human beings.